Pengaruh Media Softbook pada Perkembangan Kognitif Anak Usia Dini - Nisael Amala; Briyantika Puji Lestari; Denok Dwi Anggraini (Journal Ashil: Jurnal Pendidikan Anak Usia Dini, 2023)
This research is motivated by the low cognitive development of group A in Raudhlatul Athfal in Gampengrejo District, Kediri Regency, this is caused using contextual methods with lectures and still utilizing children's worksheets and magazines in learning, so itis less interesting and innovative. This study aims to obtain information about the effect of softbook media on cognitive development in group A children at Raudhlatul Athfal.The research method used is included in the quantitative, namely quasi-experimental with no-equivalent control group design. From a total population of 316 children, the sample in this study were 114 children in two Raudhlatul Athfal in Gampengrejo District who had undergone random sampling, the two RAs selected were RA AL-Hikmah Turus and RA AL-Azhar Ngebrak. Data analysis techniques using observation and documentation. The results obtained are by using softbook media there is a significant difference in average results between the experimental group with greater results than the control group.